2017
DOI: 10.15314/tsed.319374
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 6-weeks competition period training on body composition of boxers

Abstract: The aim of this study to investigate the effects of 6-weekscompetition period training on body composition of elite boxers. In this study, 9 elite boxers from the boxing team of the Selçuk University volunteered. Subjects were of mean age 24.11 ± 4.14 years, the experience of training 7.11 ± 3.06 years and height 179.12 ± 6.72 cm. Boxing training of the competition period was conducted for 6-weeks. The effects of the competition period training on body composition were evaluated as related to pre-and post-test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…They found that FVCbase (L) value was 2.88 ± 0.34 and FVCreference (L) value was 3.18 ± 0.36 in normal weight participants. 9 elite male boxers particioated in Akgül's (2016) study.…”
Section: Discussionmentioning
confidence: 99%
“…They found that FVCbase (L) value was 2.88 ± 0.34 and FVCreference (L) value was 3.18 ± 0.36 in normal weight participants. 9 elite male boxers particioated in Akgül's (2016) study.…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hinaus gilt eine Quadrizepsmuskelschwäche als Risikofaktor für die Entstehung einer Arthrose [66]. Akcan et al [67]betonen, dass zur Muskelstärkung mindestens drei Wochen HIIT durchgeführt werden sollten. Curran et al [65]berichteten, dass durchblutungsbeschränktes Training zusätzlich zu HIIT für acht Wochen nach der VKB-Rekonstruktion keine Veränderung des isokinetischen Spitzendrehmoments der konzentrischen Quadrizeps-Muskelkraft von 60 °/s verursachte.…”
Section: Diskussionunclassified
“…The problems of improving the effectiveness of the training process in the period before the competition were analyzed from different standpoints by Gaskov and Kuzmin (2004), Filimonov (2011), Shivit-Khurak, Galimov, and Tsyrempilov (2012), Ruddock, Wilson, Thompson, Hembrough, and Winter (2016), Akgul and Cakmakci (2017).…”
mentioning
confidence: 99%